Animal Cryptochromes: Divergent Roles in Light Perception, Circadian Timekeeping and Beyond() - Michael, Alicia K. (Photochem Photobiol, 2017)
Cryptochromes are evolutionarily related to the light-dependent DNA repair enzyme photolyase, serving as major regulators of circadian rhythms in insects and vertebrate animals. There are two types of cryptochromes in the animal kingdom: Drosophila-like CRYs that act as non-visual photopigments linking circadian rhythms to the environmental light/dark cycle, and vertebrate-like CRYs that do not appear to sense light directly, but control the generation of circadian rhythms by acting as transcriptional repressors. Some animals have both types of CRYs, while others possess only one. Cryptochromes have two domains, the photolyase homology region (PHR) and an extended, intrinsically disordered C-terminus. While all animal CRYs share a high degree of sequence and structural homology in their PHR domains, the C-termini are divergent in both length and sequence identity. Recently, cryptochrome function has been shown to extend beyond its pivotal role in circadian clocks, participating in regulation of the DNA damage response, cancer progression, and glucocorticoid signaling, as well as being implicated as possible magnetoreceptors. In this review, we provide a historical perspective on the discovery of animal cryptochromes, examine similarities and differences of the two types of animal cryptochromes, and explore some of the divergent roles for this class of proteins.